The Dangers of Money Laundering For Democracy In Indonesia - Yusuf, Hudi; Santiago, Faisal (Devotion : Journal of Research and Community Service, 2023)
Money Laundering is a serious crime. This crime occurred in several jurisdictions which made it a transnational crime. The impact caused can be detrimental to state finances and the state economy. The crime of money laundering is regulated in Law NO. 8 of 2010 article 1 paragraph 1. Democracy is a form of government in which all citizens have equal rights to make decisions that can change their lives. One form of democracy is general elections (elections) to elect national leaders. If the proceeds of crime are used as election funds, it will affect the policies of the elected leader, which will be greatly influenced by the wishes of the unscrupulous donors of funds. For example, law enforcement against crime is weak. Moreover, if the elected leader is supported by a significant vote in the legislature, then the situation will be even worse. If this is the case, it is certain that the government will no longer be able to exercise control over these criminals. Even policies in any field tend to side with the interests of the illegal financiers, therefore how the crime funds are not included in the costs of democracy